Action plans into action – An electronic action plan generation tool at a paediatric centre. (September 2020) - Elliman, Mark G.; Sloman, Peter; South, Mike; Cheng, Daryl R.
Highlights: Patient action plans have been demonstrated to be effective tools in the day-to-day management of chronic illnesses such as asthma or anaphylaxis. As documentation of patient information shifts into electronic medical records (EMR), the integration of AP generation tools provides new potential for benefit. To the authors' knowledge, this is an Australian-first study demonstrating utilisation of EMR embedded AP functionality across three key high-volume conditions. There was high uptake of an EMR-integrated AP tool for asthma, anaphylaxis and allergy across our institution. The importance of a standardised user interface for all encounters across a patient journey, is important to ensure complete and accurate AP generation. Abstract: Background: Individualised Action Plans (APs) are a key management tool for paediatric asthma, allergy, anaphylaxis and eczema. They provide salient care instructions for patients and caregivers and are thought to improve disease outcomes, albeit with minimal supporting evidence. Whilst the provision of an AP has become a widely measured healthcare quality marker, the content of the plans provided has been relatively neglected. The Royal Children's Hospital, Melbourne (RCH) implemented an AP generation tool integrated within its Electronic Medical Record (EMR) in 2017. This case study aims to exhibit the potential benefits of a hospital-wide integrated AP tool, assess its uptake and usage at our institution and demonstrate quality and user interface issues detected through audit of APs provided. Methods: A retrospective observational analysis of all APs created within the RCH EMR for patients aged 0–18 years between January 1 and December 31, 2018 was conducted. For each AP, automatically populated and clinician entered fields were extracted and analysed. Results: 2637 APs were completed during the study period. The most used AP was for asthma. Omission rates of critical information were low but could be improved. Depending on clinical condition, there was variation in both the location of completion (ED vs clinic/hospital visit) and role of clinician completing the AP (consultant vs junior medical staff). Conclusion: There was considerable uptake of an EMR-integrated AP tool across our institution. An electronic AP allowed for qualitative evaluation of usage and audit of AP content and will guide further system and user interface improvements to improve AP quality.